Pengembangan Desain Algoritma Hitung Dasar Berbantuan Program Microsoft Excel - Sawir Sawir (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2020)
The study was conducted to determine the empowerment of media design algorithm for addition, subtraction, multiplication, and distribution ( portrait ) basic calculation of how to briefly assisted by Microsoft Excel program on the motivation and learning outcomes of 24 grade IV students of SD Negeri 1 Tanjungkerta in the academic year 2018 / 2019. The research phase included: media identification, instrument simulation, media observation, product revisions, product presentations, and publications. Research data collection through the process of observation, observation, and knowledge tests. Analysis of research data is carried out quantitatively and qualitative descriptions are the basis of the research conclusions. The achievement level of students' learning motivation was 88% strongly agreed, 12% agreed, and the mean participation was 94.17%. Activities of successful student performance during the learning process reached 89.33%. In initial research there were 25% able to use the basic arithmetic algorithm for solving problems in mathematical problems. Through the final knowledge test, the research achieved learning success with the predicate of 11 students, both 7 students, and very good 3 students. Class completeness for the final knowledge competence reached 87.50%. It was concluded from the research carried out, that the application of the design media algorithm of addition, subtraction, multiplication, and division ( portrait ) short way assisted by the Microsoft Excel program is considered effective as a medium of learning mathematics.